THE MAKING OF HYDROTON WITH DIFFERENT SIZE AS GROWTH MEDIA OF HYDROPONIC FROM CLAY AND DIGESTATE - Oktafri Oktafri (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This study aimed to determine the effect of digestate composition and sizes of the granules to bulk density, water holding capacity, and the physical of hydroton. The design of this study used completely randomized factorial design with three replications. The first factor is digestate compositionwith 3 levels are 0%, 25%, and 50% to weigh of clay soil. The second factor is size particular of hydroton with 3 levels are 2-4 mm, 4-8 mm, and 8-12 mm. The results showed that there was no significant interaction between digestate composition and size of granules. However, the composition of digestateeffected to bulk density, water holding capacity, and the physicalof hydroton. The treatment combination by A3B3 was achieved the best result isthe value of bulk density media 0,83 gr/cm3, water holding capacity of 25,95%, and the physical of hydroton 11,63 N/cm2.Keywords :growth media, hydroponic, hydroton, clay soil, digestate